Iris coloration and a case of temporary heterochromia in the Red-bellied Grackle (Hypopyrrhus pyrohypogaster) (2013)
ABSTRACT: We describe overlooked patterns and age-related variation in the iris coloration of the Red-bellied Grackle (Hypopyrrhus pyrohypogaster), a range-restricted threatened species of the Colombian Andes. Whereas adults exhibit a bicolored pale yellow/scarlet red iris, juveniles show a dark iris, ranging from dark brown to grayish brown. In addition, we report the first case for a Neotropical species of temporary heterochromia iridis, an uncommon phenomenon in birds, from recaptures of a female Red-bellied Grackle in 2010. Our observations suggest that this case of heterochromia may be related to stress and changes in blood flow to the eye.